2020
DOI: 10.3168/jds.2019-18023
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of weaning strategy and solid feed location for dairy calves individually fed with an automated milk feeding system

Abstract: The objective of this study was to investigate the effect of 2 gradual weaning programs and 2 locations of solid feed within individual calf pens on feed intake, growth, and behavior of calves fed milk by an automated milk feeder. Using a 2 × 2 factorial design, 60 female calves were randomly assigned to 1 of 2 weaning treatments and 1 of 2 solid feed placement treatments. Calves were assigned to a continuous gradual weaning program (CG) or a multi-step gradual weaning program (MG). Calves assigned to the CG t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
8
1
Order By: Relevance
“…Calves on this trial experienced a high level of NCD, with 73.3% of calves being treated for NCD, regardless of treatment. This level is much higher than the 31.7% recently reported by our group that was conducted at the same facility (Parsons et al, 2020) and the 21.4% reported for digestive issues in North America (Urie et al, 2018).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Calves on this trial experienced a high level of NCD, with 73.3% of calves being treated for NCD, regardless of treatment. This level is much higher than the 31.7% recently reported by our group that was conducted at the same facility (Parsons et al, 2020) and the 21.4% reported for digestive issues in North America (Urie et al, 2018).…”
Section: Discussioncontrasting
confidence: 60%
“…A power analysis (Morris, 1999;Hintze, 2008) was performed before the study for the primary response variables, including feed intake and BW. Estimates of variation for these variables (mean CV = 15%) were based on previously reported values (Eckert et al, 2015;Overvest et al, 2016;Parsons et al, 2020). From the power analysis, it was determined that at 80% power, treatment differences of ~8% could be detected at this sample size (n = 30 calves per treatment combination).…”
Section: Study Design and Treatmentsmentioning
confidence: 99%
“…Previous studies with calves have demonstrated that decreasing the milk allowance during the artificial milk feeding period or optimizing the type of solid feed (e.g., presentation form and taste) and feeder location prior to weaning can encourage young ruminants to increase the solid feed intake ( 1 , 4 ). However, artificial milk feeding in conjunction with early weaning strategies can limit the rumen microbiological colonization by a microbial consortium able to perform the major fermentative and metabolic functions required at weaning and beyond, which may have negative effects on the weaning process ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial milk represents a substantial feeding cost in the current production systems, but weaning is not recommended until the rumen has a sufficient anatomical, physiological, and microbiological development ( 3 ), particularly when early weaning (conventional) is performed at 2 months of age. Several nutritional strategies have been proposed to maximize the solid feed intake prior to weaning such as decreasing milk allowance (step-down weaning) or optimizing feeder location and type of solid feed ( 1 , 4 ). Nevertheless, these strategies are unlikely to favor the rumen microbial development.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the intensive milk or MR feeding program, more attention must be paid to weaning (Meale et al, 2017;Mirzaei et al, 2020). Reducing milk or MR feeding too fast or too early may result in impaired growth and development during the weaning process (Mirzaei et al, 2018;Welboren et al, 2019;Parsons et al, 2020).…”
Section: Introductionmentioning
confidence: 99%